The effect of sexual stratification by race on arrest in sexual battery cases - Myers, Howard P. (American journal of criminal justice, 1985)
LaFree finds that in most respects officials react more seriously to black assailants who assault white victims than other suspects. Yet paradoxically black assailants who assault white victims are not more likely to be arrested. He explains this apparent inconsistency by proposing that place of incarceration or length of sentence have to do with the seriousness of the offense, whereas arrest has to do with whether the assailant is guilty or innocent. This paper rejects that distinction, arguing that both involve judgments that reflect the influence of similar factors. Several such factors are examined in an analysis of 347 offense reports on sexual battery in Tallahassee over a recent five-year period. The data show that exceptionally cleared cases are the rule in black assailant-black victim (BB) rapes where victims and assailants are mostly acquainted, whereas cases pending predominate in black assailant-white victim (BW) rapes where victims and assailants are mostly strangers. When victims and assailants are acquainted, proportionately more arrests are made in BW rapes than in BB rapes. These findings are consistant with conflict theory’s position that powerful groups enforce sexual-property rules by the differential application of criminal law and punitive sanctions.